2013
DOI: 10.1093/intimm/dxt051
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and immunological characterization of β′-component (Onc k 5), a major IgE-binding protein in chum salmon roe

Abstract: Salmon roe has a high allergic potency and often causes anaphylaxis in Japan. The major allergic protein of salmon roe is β'-component, which is a 35kDa vitellogenin fragment consisting of two subunits. To elucidate structural information and immunological characteristics, β'-component and the subunit components were purified from chum salmon (Onchorhincus keta) roe and vitellogenin-encoding mRNA was used to prepare β'-component subunit-encoding cDNA. This was PCR-amplified, cloned and sequenced and the deduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…2, chum salmon β"-component as an immunized antigen showed a high purity. Lipovitellin heavy chain (around 90 kDa) was found to be the predominant component in all fish yolk extracts, and the 16 kDa and 18 kDa subunits of β"-component (Shimizu et al, 2014) were observed in chum salmon YEx. In the immunoblot analysis (Lane3), protein components detected by anti-β(Rabbit) were also found in the all other fish YEx, except for Pacific herring.…”
Section: Detection Of β'-Component In Fish Yolk Extractmentioning
confidence: 94%
See 1 more Smart Citation
“…2, chum salmon β"-component as an immunized antigen showed a high purity. Lipovitellin heavy chain (around 90 kDa) was found to be the predominant component in all fish yolk extracts, and the 16 kDa and 18 kDa subunits of β"-component (Shimizu et al, 2014) were observed in chum salmon YEx. In the immunoblot analysis (Lane3), protein components detected by anti-β(Rabbit) were also found in the all other fish YEx, except for Pacific herring.…”
Section: Detection Of β'-Component In Fish Yolk Extractmentioning
confidence: 94%
“…β′-component has been registered as a new allergen named "Onc k 5" in the official allergen list of the World Health Organization and International Union of 6 Immunological Societies Allergen Nomenclature Subcommittee in 2012 (http://www.allergen.org/). β′-component is a homodimer protein composed of two isoform subunits with similar allergenic identity (Shimizu et al, 2014), and the IgE-binding sites (IgE epitopes) in β′-component showed strong proteolytic resistance (Fujita et al, 2012), which may account for its strong allergenicity as a food allergen.…”
mentioning
confidence: 99%
“…Ingestion of fish roe may also lead to allergic sensitization and clinical allergy. The allergen Onc k 5 (chum salmon) is vitellogenin, a 118 kDa protein and precursor of yolk proteins [74]. Roe allergens from different fish species are cross-reactive but there is no cross-reactivity to hen's egg or fish muscle allergens.…”
Section: Other Fish Allergensmentioning
confidence: 99%
“…In Japan, SR is the fifth most common food allergen , and it can cause anaphylactic reactions in small children . Using sera from several SR‐allergic patients, the beta‐component was identified as the main allergen . There is no IgE cross‐reactivity between SR and hen's egg allergies; nevertheless, in Japan, many patients with hen's egg allergies eliminate SR because SR is ‘an egg’ of fish.…”
Section: Comparison Of Patients' Profiles and Laboratory Data Betweenmentioning
confidence: 99%
“…Nevertheless, the main allergen for SR was not egg phosvitin. The beta‐component was identified as the main allergen. There was cross‐reactivity between SR and herring roe, but no relationship between SR and hen's egg .…”
Section: Comparison Of Patients' Profiles and Laboratory Data Betweenmentioning
confidence: 99%